2018
DOI: 10.1080/21681805.2018.1498124
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic pathway efficacy for urinary tract cancer: population-based outcome of standardized evaluation for macroscopic haematuria

Abstract: Objective: This study assessed a national healthcare intervention launched in Sweden in 2015 to reduce the time between macroscopic haematuria, diagnosis and treatment of urinary tract cancer. Methods: The outcome of the first 11 months was evaluated in 1697 individuals referred to a standardized care pathway for urinary tract cancer compared with 174 patients with conventionally diagnosed urothelial carcinoma. Results: Among the referred individuals, 317 (19%) were diagnosed with cancer, 1034 (61%) had a beni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…The main bias and applicability concerns related to the suboptimal identification and/or adjustment for confounders in 18 of the studies, 6 of which were studies using questionnaires,14–19 10 were retrospective cohort studies providing descriptive statistics mainly, using record reviews (n=5)20–24 and electronic health records (n=5),25–29 1 was a case–control study30 and 1 an ecological study 31…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The main bias and applicability concerns related to the suboptimal identification and/or adjustment for confounders in 18 of the studies, 6 of which were studies using questionnaires,14–19 10 were retrospective cohort studies providing descriptive statistics mainly, using record reviews (n=5)20–24 and electronic health records (n=5),25–29 1 was a case–control study30 and 1 an ecological study 31…”
Section: Resultsmentioning
confidence: 99%
“…Ten of the 20 studies which extracted symptom information used coded information from routine or claims data,21 25 28 29 31 34 35 37–39 5 used self-reported symptoms from questionnaire and audit data,14–16 19 40 6 studies performed direct record review22 24 25 30 33 41 and 1 used coded information and record review 17…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue, Nilbert and colleagues present an evaluation of the standard pathway of care for haematuria introduced in Sweden in 2015 (1). Compared to patients diagnosed by conventional referral, they found that the diagnostic delay time from occurrence of haematuria to diagnosiswas reduced with median 10 days, from 35 to 25.…”
Section: Editorialmentioning
confidence: 99%